Timed Ang2-targeted therapy identifies the Angiopoietin-tie pathway as key regulator of fatal lymphogenous metastasis - Gengenbacher, Nicolas; Singhal, Mahak; Mogler, Carolin; Hai, Ling; Milde, Laura; Abdul Pari, Ashik Ahmed; Besemfelder, Eva; Fricke, Claudine; Baumann, Daniel; Gehrs, Stephanie; Utikal, Jochen; Felcht, Moritz; et al. (Cancer discovery, 2021)
Recent clinical and preclinical advances have highlighted the existence of a previously hypothesized lymphogenous route of metastasis. However, due to a lack of suitable preclinical modeling tools, its contribution to long-term disease outcome and relevance for therapy remain controversial. Here, we established a genetically engineered mouse model (GEMM) fragment-based tumor model uniquely sustaining a functional network of intratumoral lymphatics that facilitates seeding of fatal peripheral metastases. Multiregimen survival studies and correlative patient data identified primary tumor-derived Angiopoietin-2 (Ang2) as a potent therapeutic target to restrict lymphogenous tumor cell dissemination. Mechanistically, tumor-associated lymphatic endothelial cells (EC), in contrast to blood vascular EC, were found to be critically addicted to the Angiopoietin-Tie pathway. Genetic manipulation experiments in combination with single-cell mapping revealed agonistically acting Ang2-Tie2 signaling as key regulator of lymphatic maintenance. Correspondingly, acute presurgical Ang2 neutralization was sufficient to prolong survival by regressing established intratumoral lymphatics, hence identifying a therapeutic regimen that warrants further clinical evaluation. - Significance: Exploiting multiple mouse tumor models including a unique GEMM-derived allograft system in combination with preclinical therapy designs closely matching the human situation, this study provides fundamental insight into the biology of tumor-associated lymphatic EC and defines an innovative presurgical therapeutic window of migrastatic Ang2 neutralization to restrict lymphogenous metastasis.This article is highlighted in the In This Issue feature, p. 211